2008
DOI: 10.1088/1748-6041/3/1/015005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yttria addition on mechanical, physical and biological properties of bioactive MgO–CaO–SiO 2 –P 2 O 5 –CaF 2 glass ceramic

Abstract: Preparation of the bioactive MgO-CaO-SiO2-P2O5-CaF2 glass was carried out utilizing tap casting and powder metallurgy methods. The original composition was modified with 0.2% Y2O3 and carbon additions. The mother and the modified bioglass were examined, and comparative studies were performed between the mother and modified type to study the compositional modification effects on physical, mechanical and biological properties. The histology of mother type showed that this type has a good biocompatibility with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…[16,22,28,31] Different studies concentrate on the twocomponent alloy system magnesium-calcium; they basically report on the constant corrosion rate and the possibility to adjust the corrosion, the biomechanical properties, and the biocompatibility by alloying different amounts of calcium. [28,[32][33][34][35] An adjustable and constant corrosion seems to be required to predict the period of degradation and to estimate the tissue reactions due to degradation products.…”
mentioning
confidence: 99%
“…[16,22,28,31] Different studies concentrate on the twocomponent alloy system magnesium-calcium; they basically report on the constant corrosion rate and the possibility to adjust the corrosion, the biomechanical properties, and the biocompatibility by alloying different amounts of calcium. [28,[32][33][34][35] An adjustable and constant corrosion seems to be required to predict the period of degradation and to estimate the tissue reactions due to degradation products.…”
mentioning
confidence: 99%
“…5 Different metal ions, such as Zn, Co, Cu, Sr, Ag, Ti, La, Ce, B, In, Ga and Y, have been added in bioactive glasses or glass ceramics to achieve different aims. [7][8][9][10][11][12][13] This topic was well reviewed by Hoppe et al and Habibovic et al 6,14 Nevertheless, there are only a few reports on Eu doped bioactive glasses and glass ceramics to our knowledge. But according to the results from previous studies, the incorporation of Eu to biomaterials has great potential for using in the biomedical field.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, improved mechanical properties can be expected as the results of the substitution of rare earth for CaO in the glass ceramics. 10,13 Thirdly, but not lastly, Eu 3z ions fluoresce well a red colour and have been utilised extensively in colour televisions and high efficiency fluorescent lamps. 18 Recently, much attention has been attracted on applying its luminescent property in biomedical field.…”
Section: Introductionmentioning
confidence: 99%
“…HA is usually employed for this application because its chemical composition is similar to that of the mineral phase of natural bone. , Because of the inferior mechanical behavior of HA, efforts have been devoted to the development of composites, with a focus on improving the physical, mechanical, and biological properties of these materials. Recent studies have demonstrated that the addition of Y 2 O 3 to HA improves the mechanical behavior of the composite materials while maintaining good biocompatibility. The incorporation of Y 2 O 3 dispersed into the HA favors the sintering process and controls the decomposition mechanisms of HA into calcium phosphates, which makes HA + Y 2 O 3 composites promising materials for orthopedic metallic implant coatings with improved mechanical and functional properties.…”
Section: Introductionmentioning
confidence: 99%